Health risk assessment resulting from the presence of Legionella bacteria in domestic hot water in public buildings – the results of a pilot study - Kmiecik, Ewa; Wątor, Katarzyna; Chochorek, Aneta; Kołodziej, Mateusz; Mika, Anna; Krawiec, Arkadiusz; Herzig, Janusz (Geology, Geophysics and Environment, 2021)
The aim of the study was to assess the risk posed by Legionella bacteria in a public building in Krakow. An old building with internal installation risers of different ages, as well as draw-off points of different types, was selected for testing. Samples were collected during two campaigns. In one sample of the first series of tests, no bacteria were found. During the second series of tests, no Legionella bacilli were found in just one sample and in one sample only 4 colony-forming units were detected. At the remaining draw-off points (water taps), the bacteria count detected were greater than the maximum threshold allowed by legal regulations (admissible threshold for public utility buildings – 100 cfu/100 mL). No morphological differences were observed with respect to the occurrence of specific serogroups. In 14 samples, Legionella pneumophila serogroups 2–14 were found, while the Legionella pneumophila serogroup 1 was only found in one sample. The risk assessment was also carried out based on a semi-quantitative risk matrix approach and as a quantitative microbial risk assessment. The risk matrix approach was successfully implemented for the recognition of the potential risk associated with the Legionella occurrence in a water system. The calculated annual cumulative risk is high. The research shows that even if the weekly inhalation exposure dose (and therefore the calculated risk) is high, the number of Legionella pneumophila illness cases found can be equal to zero. This is probably due to the large uncertainty associated with QMRA determination. The size of the room in which the contaminated water is used also affects the possibility of infection.